Setting critical limits to ecological indicators of sustainable tropical forestry - Geisler, C.C.; Ghazoul, J.; Hellier, A. (2000)
Ecologically sustainable forest management necessitates monitoring forest conditions and the environmental impacts of management activities. Through adaptive management, assessments that reveal excessive environmental impacts require revision of the management plan to ensure that ecological functions and attributes of forest ecosystems are maintained within acceptable limits. But how are these acceptable limits determined? And how are 'normal' or 'natural' conditions defined when these are temporally or spatially variable? In order to determine the desired biological state of a forest, indicator baseline values, together with some measure of variability under natural conditions are needed. A useful Ecological Criteria and Indicator set should therefore provide objective standards for evaluation, and these standards should account for spatial and temporal variation in indicator states as well as resilience to anthropogenic disturbance. A framework is presented within which the standards for assessing ecologically sustainable forest management might be defined. Published literature is used to determine the responses of selected indicators to natural and anthropogenic disturbances. Using these values, predictions can be made on expected ecological conditions of a sustainably managed forest given information on forest type, disturbance intensity and time since disturbance.